The Potential of Silence in Education: Methodological and Didactic Prerequisites - A. D. Korol (Высшее образование в России)
This paper investigates philosophical, cultural and didactic potential of silence in education. The author substantiates that in the world of ever-augmenting speaking, the student’s silence is manifested as a stage, when there is nothing to say for oneself. This is attributable to the monologue nature of education, the main meanings, goals and the content of which is to convey the multicultural experience of mankind to a “monocultural” student. At the same time, there is a huge potential for silence as competence whereby a student generates his new meanings, knowledge, questions. The paper presents a comparative analysis of the didactics of Eastern and Western cultures core parameters as creativity, dialogism, interactivity. The author concludes that despite the sufficiently large number of the silence phenomenon studies in pedagogy, they mainly affect the methodical le[1]vel. In reliance on philosophical, linguistic, psychosocial research, the article originally examines the methodological foundations of the design and implementation of the didactics of silence. Particular attention is paid to the links between silence, “questioning” and heuristics. It is indicated that silence in teaching factors into exponential development and the formation of such future competencies as creativity, communication, and the affective sphere.